Antiangiogenic therapy for breast cancer with triple negative phenotype - Inna P. Ganshina (IP Habib O.N., 2021)
Triple-negative breast cancer is 1024% of all cases of breast cancer and is characterized by the absence of estrogen, progesterone, and HER-2 receptors in the tumor. The therapy of this illness is a difficult clinical case. In contrast to hormone-positive and HER-2-positive phenotypes, in which we successfully use targeted drugs (antiestrogens and anti-HER-2 drugs), for triple-negative breast cancer we have not had such targets for a long time. Thus, despite the impressive results of immunotherapy of triple-negative breast cancer, there remains a fairly large group of patients with negative PD-L1 status, for whom it is necessary to develop other treatment strategies. One of the approaches in the treatment of malignant tumors includes not the impact on tumor cells, but the process of angiogenesis. Antiangiogenic drugs have positively proven themselves in the treatment of a large number of malignant tumors but are underestimated for breast cancer (including triple-negative phenotype). The use of bevacizumab in combinations with cytostatic drugs in breast cancer therapy (including triple-negative breast cancer) has been studied in a large number of clinical trials but was undeservedly forgotten in some countries due to the revoked FDA registration. This review presents the role of bevacizumab in the treatment of patients with triple-negative breast cancer and suggests the conditions when the administration of this drug is justified and leads to better results.